The processes and context of innovation in mental healthcare: Oxfordshire as a case study. Issue 1 (March 2023) - Hall, John; Armstrong, Neil; Agulnik, Peter; Fees, Craig; Kennard, David; Leach, Jonathan; Millard, David
This article introduces the four following articles and the Classic Text. They describe the development of a sequence of innovative local mental health services in Oxfordshire, and explore the processes of innovation, led by the humane pragmatism practised by Dr Bertram Mandelbrote, who was Physician Superintendent at Littlemore Hospital in Oxford from 1959 to 1988. The articles describe emerging patterns of therapeutic community practice, and trace the events leading to a set of discrete service developments outside the hospital. Together, they suggest a positive role for chance in these developments, and a focus on the then prevailing national and local regulatory culture. The Classic Text by David Millard provides an overview of the origins of the therapeutic community movement.